Basic life support skills and health emergency preparedness among school teachers in India: a questionnaire-based study in an urban population - Srinivasan, Ranjiini; Krishnan, Surya G.; Bhojaraja, Shashank; Srinivasan, Mithuna (International Journal Of Community Medicine And Public Health, 2019)
Background: The purpose of this study was to assess basic life support (BLS) knowledge and attitudes among school teachers in India, and to elicit school preparedness in handling medical emergencies. Methods: Using a two stage sampling technique, 198 teachers from 10 schools in a metropolitan city participated in the study. A pre-validated questionnaire was administered to assess school teacher knowledge of BLS, and the principals of the schools provided information regarding the facilities available to manage health emergencies. Results: Although more than half of the surveyed teachers were aware of the term BLS, only 7 percent were trained in resuscitation. Thirteen percent of teachers had encountered emergencies in the classroom. Most of the schools maintained a basic first aid kit but lacked other equipment necessary to manage more serious health emergencies. Conclusions: Our study suggests that although teachers may be aware of BLS, they lack formal training and schools may be poorly equipped to tackle medical emergencies. It is therefore necessary to regularly train teachers in BLS and ensure that schools are provided with resuscitation equipment to enable them to handle health emergencies in children.